GOOD CORPORATE GOVERNANCE (GCG) TERHADAP SOLVABILITAS PERUSAHAAN ASURANSI JIWA SYARIAH DI INDONESIA - Lina Adbiyah; zubaidah Nasution; Mellyza Silvy; Surya Setiawan (JES (Jurnal Ekonomi Syariah), 2023)
The purpose of this study is to analyze the influence of Good Corporate Governance (GCG) and the Return on Investment Ratio toward Solvency in Islamic Life Insurance Companies in Indonesia. This study uses a quantitative approach using secondary data. The population of this study is all Sharia Life Insurance Companies in Indonesia with the 2017-2021 research period. The sampling technique uses purposive sampling method. Samples that met the criteria were 18 Sharia Life Insurance from 23 Sharia Life Insurance in Indonesia. The model used as an analysis tool is multiple regression analysis. Data processing in this study uses SPSS 25.0 tools. The results of this study indicate that simultaneously the variables of the Board of Commissioners, Board of Directors and Investment Return Ratio have a positive and significant effect on Solvency (RBC) on Sharia Life Insurance in Indonesia. Whereas the Board of Commissioners partially has a negative and significant effect on Solvability (RBC). In addition, Board of Directors has a negative and significant effect on Solvability (RBC) and the Return on Investment Ratio has no effect on Solvability (RBC).